CO-TEACHING IN THE EARLY YEARS: COLLABORATIVE PERSPECTIVES BETWEEN GENERAL EDUCATION AND ENGLISH LANGUAGE INSTRUCTION - Ildebrand, Isaías dos Santos; Matté, Mélany Blume; Niedermeier, Fabiana (Revista Conhecimento Online: Diversidade e Inclusão Social, 2025)
The article discusses co-teaching in the early years of elementary education, emphasizing the collaborative work between classroom teachers and English language teachers. Based on a nonsystematic literature review, the study brings reflections on co-teaching, multicultural curriculum, and collaborative pedagogical practices. Grounded in co-teaching models and critical approaches, it analyzes how shared teaching can contribute to the reconfiguration of school practices. The findings highlight that this approach enhances pedagogical listening, strengthens integrated planning, and promotes more situated educational actions. The impact of co-teaching on teacher education and the organization of pedagogical work is also emphasized, particularly the roles of school leadership and continuing education. The article concludes that co-teaching represents a promising path for education and classroom practices, especially in contexts marked by linguistic and cultural diversity.